2018
DOI: 10.3906/vet-1712-43
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IgG and semiquantitative tests for evaluation of passive transfer immunity in calves

Abstract: Serum immunoglobulin (IgG) and semiquantitative tests are used for the evaluation of passive transfer immunity (PTI) in calves. We aimed to evaluate PTI in calves by using a Brix refractometer, total protein (TP), gamma-glutamyl transferase (GGT), and glutaraldehyde coagulation test (GCT) on days 1, 3, and 7 after birth; to compare the results with serum IgG; and to evaluate which day these tests are given on will give the best results. The blood samples were collected from 60 Holstein dairy calves on day 0, j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
(57 reference statements)
4
7
0
Order By: Relevance
“…In the present study, Brix% results of goats kids on day one are similar to the results of Oman et al [24]. Furthermore, in the present study it was observed that, similar to a study conducted in calves [22], Brix% and TP levels were higher in the first 3 days when compared to presuckling levels. The higher Brix% and TP levels compared to IgG on the first day could be related to the absorption of solids other than immunoglobulin from the colostrum as colostrum is reported to contain 7%-13% fat, 4%-10% nonimmunoglobulin proteins, and 2%-5% lactose [4].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, Brix% results of goats kids on day one are similar to the results of Oman et al [24]. Furthermore, in the present study it was observed that, similar to a study conducted in calves [22], Brix% and TP levels were higher in the first 3 days when compared to presuckling levels. The higher Brix% and TP levels compared to IgG on the first day could be related to the absorption of solids other than immunoglobulin from the colostrum as colostrum is reported to contain 7%-13% fat, 4%-10% nonimmunoglobulin proteins, and 2%-5% lactose [4].…”
Section: Discussionsupporting
confidence: 91%
“…GGT enzyme activity also reached the highest level on day 1 and decreased between days 2 and 3 (P < 0.01). The rapid decrease in GGT after the first day is similar to the results from other studies of goat kids [18], lambs [12], and calves [22,29]. Thus, we can suggest that among the semiquantitative tests, GGT is an early indicator for determining FPT in goat kids.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations